Burns and socioeconomic deprivation: the experience of an adult burns centre. Issue 8 (December 2021) - Snelling, Samuel; Challoner, Thomas; Lewis, Darren
Highlights: Burns incidence increases with higher rates of socioeconomic deprivation. Patients living in areas with the highest socioeconomic deprivation are less likely to perform first aid. Certain mechanisms of injury are more in areas of highest deprivation, such as assault and self-harm. Abstract: Introduction: Burns incidence, mortality and complication rates have been shown to be directly correlated by race, gender and socioeconomic status. As such, socioeconomic status (SES) has been previously highlighted as a target for burn prevention in the UK and abroad. The Queen Elizabeth Hospital, Birmingham (QEHB) is the regional Burns Centre for the Midlands Burn Network, supporting a population of 13.7 million Methods: 16-year retrospective review was performed of all acute adult burns assessed by the Burns and Plastics Department, QEHB. The data included patient demographics (age, gender, ethnic origin and postcode), mechanism of injury, total body surface area (TBSA) affected and whether first aid was given. IMD Rank, IMD Scores were obtained from individual postcodes, as well as incidence data per electoral ward. Results: In our analyses there were 3369 total acute admissions and acute assessments. 812 patients (24.1%) were in the most deprived decile. 1715 patients (50.9%) live within the 3 most deprived deciles. The deciles with the lowest completion of first aid were the first (524, 70.72%), third (257, 72.39%) and second (351, 72.82%). Conclusions: This study shows patients from the most deprived areas are over-represented in burns incidence and are less likely to perform first aid. We feel this should be highlighted in burns prevention and education strategies.